ICD-10 Coding Will Challenge Researchers- Caution and Collaboration May Reduce Measurement Error and Improve Comparability Over Time - Mainor, Alexander J. (Med Care, 2019)
BACKGROUND: The October 1, 2015 U.S. healthcare diagnosis and procedure codes update, from the 9th to 10th version of the International Classification of Diseases (ICD), abruptly changed the structure, number and diversity of codes in healthcare administrative data. Translation from ICD-9 to ICD-10 risks introducing artificial changes in claims-based measures of health and health services. OBJECTIVE: Using published ICD-9 and ICD-10 definitions and translation software, we explored discontinuity in common diagnoses to quantify measurement changes introduced by the upgrade. DESIGN: Using 100% Medicare inpatient data, 2012–2015, we calculated quarterly frequency of condition-specific diagnoses on hospital discharge records. Years 2012–2014 provided baseline frequencies and historic, annual fourth quarter changes. We compared these to quarter four of 2015, the first months after ICD-10 adoption, using Centers for Medicare and Medicaid Chronic Conditions Warehouse (CCW) ICD-9 and ICD-10 definitions and other commonly-used definitions sets. RESULTS: Discontinuities of recorded CCW-defined conditions in quarter four of 2015 varied widely. For example, compared to diagnosis appearance in 2014 quarter four, in 2015 we saw a sudden 3.2% increase in chronic lung disease and a 1.8% decrease in depression; frequency of acute myocardial infarction was stable. Using published software to translate Charlson-Deyo and Elixhauser conditions yielded discontinuities ranging from −8.9% to +10.9%. CONCLUSION: ICD-9 to ICD-10 translations do not always align, producing discontinuity over time. This may compromise ICD-based measurements and risk-adjustment. To address the challenge, we propose a public resource for researchers to share discovered discontinuities introduced by ICD-10 adoption and the solutions they develop.